The accessibility of HIV-infected Poor Women to the Prevention of Mother to Child Transmission Service in Surakarta Indonesia - Demartoto, Argyo; Zunariyah, Siti; Soemanto, Robertus Bellarminus (Indian Journal of Community Health, 2016)
Background: HIV transmission from HIV-infected mother to child can occur through pregnancy, birth and lactation process; therefore, there should be Prevention of Mother to Child Transmission or PMTCT. Aims & Objectives: This research aimed to study the HIV-infected poor women’s accessibility to the Prevention of Mother to Child Transmission Service in Surakarta Indonesia. Material & Methods: This study was a qualitative research with explorative approach conducted in October-December 2015 and HIV-infected poor women as the unit of analysis. The sampling technique used was maximum variation sampling. Techniques of collecting data used were observation, in-depth interview and documentation, while data analysis was conducted using an Interactive Model of analysis with materialist theory. Results: Structural, financial and personal or cultural constraints were found: less target-appropriate health insurance policy, expensive cost of delivery with section caesarian surgery and breastfeed-substituting formula milk, and limited knowledge, experience and negotiation with the service provider leading to the HIV-infected Poor Women’s limited accessibility to comprehensive and sustainable PMTCT. PMTCT socialization, the giving-birth insurance and Food Supplementation program activation by Empowerment Work Group in AIDS Coping Commission in Surakarta City was the opportunity to access PMTCT service. Conclusion: Although PMTCT resulted in some problems, particularly formula milk administration and delivery process with section caesarian surgery, this attempt should be taken to make the baby born healthy. For that reasons, PMTCT service and health insurance should be improved from beneficiary data to accessible and sustainable procedure.